What is the best available science? A comparison of marine scientists, managers, and interest groups in the United States. (March 2016) - Wolters, Erika Allen; Steel, Brent S.; Lach, Denise; Kloepfer, Daniel
Abstract: In recent years there have been calls among decision makers, interest groups, citizens, and scientists alike for the use of the "best available science" when making environmental policy and managing natural resources. The assumption is that including scientists and the best available scientific information will improve the quality of complex policy decisions. Others have argued, however, that science and scientists are just one source of expertise concerning environmental management and increasing involvement will not necessarily lead to better policy. We report on a study examining the attitudes and orientations of marine scientists, resource managers, and interest group representatives concerning factors that may affect scientific credibility, the credibility of scientific research produced by various organizations, and perceptions of the ability of certain groups to understand scientific research. Using national random sample surveys and interviews of marine scientists, marine managers, and interest groups involved in marine policy issues conducted in 2011, we examine indicators of scientific credibility, data, research and reputation; the ability of scientists to communicate findings; and the role of scientists in the policy process. Further, we explore what factors contribute to credible science, the credibility of the science produced by various organizations, and the scientific literacy of various policy actors. Highlights: We examine indicators of scientific credibility, data, and research and reputation. We analyse scientist's ability to communicate findings. Scientific credibility and communication are key to public policy formation. There is a balance between perceived advocacy and credibility. We find that policymakers and resource managers want more scientific guidance.